Kedudukan Perempuan dalam Sejarah Islam dan Pengaruhnya terhadap Hukum Keluarga Islam di Indonesia (Studi Analisis Kompilasi Hukum Islam) - Rohmansyah; Rizki, Darlin (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Socio-historically, the role and contribution of women often do not receive the attention they deserve in the history of Islamic civilization. Many historical records tend to emphasize male figures and ignore or underestimate the contributions of women. This creates a significant gap in understanding regarding the position and role of women in Islamic history. This paper tries to describe two things. First, the position of women in Islamic history. Second, the implications of women's position in Islamic history on Indonesian family law. Because, basically, the process of forming laws in Indonesia is the position of women in the past. This type of research, using literature research with the research properties of descriptive-prescriptive analysis. While the approach used is the historical approach. The results of this study show: First, the portrait of the position of women in Islamic history, especially in pre-Islamic and Islamic thought (interpretation and jurisprudence) women are placed in the second position after men. Second, the family law that was formed was a lot of descriptive content, exploitation, because it was formed based on the history of women's position in Islam which was charged with male culture.